Assessment of performance efficiency of enterprises producing electricity in hydro and wind power plants - Bobinaitė, Viktorija; Juozapavičienė, Aldona (Business: Theory and Practice, 2011)
The system of indicators for assessment of performance efficiency of enterprises producing electricity in hydro and wind power plants is presented in this article. The financial relative indicators are taken from balance and profit (loss) sheets of analyzed enterprises. Three groups of financial relative indicators are calculated. They are as follows: profitability, turnover and solvency. The analysis of profitability showed that because of rapidly increasing costs, the profitability of enterprises producing electricity in hydro and wind power plants had been deteriorating in recent years and for some years had been negative. The analysis of solvency indicators represented that liability of enterprises and risk had increased and liquidity had decreased. Asset turnover indicators told that the efficiency of resources, which were used in activity, had reduced. Article in Lithuanian. Elektros energiją vėjo ir hidroelektrinėse gaminančių įmonių veiklos efektyvumo vertinimas Santrauka. Straipsnyje pristatoma elektros energiją vėjo ir hidroelektrinėse gaminančių įmonių veiklos efektyvumo vertinimo rodiklių sistema, grindžiama pagrindinių finansinių ataskaitų (balanso ir pelno (nuostolio) ataskaitos) straipsniais. Darbe nagrinėjamos trys rodiklių grupės: pelningumo, apyvartumo ir mokumo. Pelningumo rodiklių analizė parodė, kad dėl sparčiai augančių išlaidų, energiją vėjo ir hidroelektrinėse gaminančių įmonių veiklos pelningumas pastaruoju metu prastėjo, o kai kuriais metais buvo net neigiamas. Mokumo rodiklių analizė parodė, kad įmonių įsiskolinimas ir rizika didėjo, o likvidumas mažėjo. Turto apyvartumo rodiklių skaičiavimas atskleidė, kad ūkinėje įmonių veikloje sunaudojamų išteklių efektyvumas mažėjo. Reikšminiai žodžiai: atsinaujinantieji energijos ištekliai, vėjo jėgainė, hidroelektrinė, efektyvumas, finansiniai santykiniai rodikliai, pelningumas, apyvartumas, mokumas.